2008
DOI: 10.1016/j.concog.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual enhancement of touch and the bodily self

Abstract: In Press, Consciousness and CognitionWord Count: 4,388 Touch and the Body 2 Abstract We experience our own body through both touch and vision. We further see that others' bodies are similar to our own body, but we have no direct experience of touch on others' bodies.Therefore, relations between vision and touch are important for the sense of self and for mental representation of one's own body. For example, seeing the hand improves tactile acuity on the hand, compared to seeing a non-hand object. While seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 43 publications
7
68
1
Order By: Relevance
“…Such visual modulation of bodily signals is also reflected in the tactile domain, as seeing one's hand improves tactile acuity on the hand, compared to seeing a nonhand object (visual enhancement of touch [40]). This latter effect is further boosted by hand ownership manipulations [41], as revealed by the crossmodal congruency effect for hands [42] and avatars [43]. Taken together, these results highlight the role of visual signals in experimentally and neurologically induced altered states of BSC.…”
Section: Influences Of Vision On Bodily Self-consciousnesssupporting
confidence: 50%
“…Such visual modulation of bodily signals is also reflected in the tactile domain, as seeing one's hand improves tactile acuity on the hand, compared to seeing a nonhand object (visual enhancement of touch [40]). This latter effect is further boosted by hand ownership manipulations [41], as revealed by the crossmodal congruency effect for hands [42] and avatars [43]. Taken together, these results highlight the role of visual signals in experimentally and neurologically induced altered states of BSC.…”
Section: Influences Of Vision On Bodily Self-consciousnesssupporting
confidence: 50%
“…It is currently unclear which aspect of seeing the hand is responsible for the present effects. One previous study found that the enhancing effect of seeing one's body on touch was linked primarily to sense of ownership (Longo et al, 2008a). In contrast, other effects, such as acceleration of visual reaction times (Longo and Haggard, 2009) and proprioceptive integration (Tsakiris et al, 2006), appeared to be related to agency.…”
Section: Discussionmentioning
confidence: 93%
“…In a control condition, participants saw the mirror image of a non-hand object. The mirror box provides an elegant experimental means of manipulating vision of the body while keeping vision non-informative about stimulation and has been used for this reason previously (Harris et al, 2007;Longo et al, 2008a;Moseley and Wiech, 2009). We measured subjective ratings of pain intensity and unpleasantness, using a visual-analog scale (VAS) and cortical processing using LEPs.…”
Section: Introductionmentioning
confidence: 99%
“…This question relates to the sufficient and necessary conditions to attribute an external object to our body. The second experiment suggests that mere exposure to the rubber hand is not enough to induce a full-blown embodiment of the RH [24]. We hypothesized that expectations about upcoming sensory events with respect to a rubber hand are sufficient to induce an SO over the same rubber hand, as measured by questionnaire and SCR.…”
Section: Discussionmentioning
confidence: 99%